2020
DOI: 10.1007/s00259-020-05041-0
|View full text |Cite
|
Sign up to set email alerts
|

Management of differentiated thyroid cancer through nuclear medicine facilities during Covid-19 emergency: the telemedicine challenge

Abstract: Purpose To investigate whether a telemedicine service (TMS) carried out during the Covid-19 pandemic impacted on management of patients with differentiated thyroid cancer (DTC). Methods We retrospectively reviewed the number and the findings of outpatient visits in DTC subjects referred between March 11, 2020, and May 31, 2020, during the Covid-19 pandemic at the Radiometabolic Unit of the University of Naples Federico II. Office visits scheduled in March and May 2020 were converted in teleconsultation reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Studies from various countries have suggested that thyroid cancer care has been significantly impacted by the COVID-19 pandemic, including reports of reductions in: fine needle aspiration biopsies of thyroid nodules [2,3], outpatient visits [3], thyroid surgery volumes [2], and radioactive iodine ablation [3]. Furthermore, virtual care has been increasingly adopted in thyroid cancer outpatient care [4]. Virtual care may be defined as "any interaction occurring remotely between patients and/or members of their circle of care, through any form of communication or information technology with the aim of facilitating or maximizing the quality and effectiveness of patient care" [5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies from various countries have suggested that thyroid cancer care has been significantly impacted by the COVID-19 pandemic, including reports of reductions in: fine needle aspiration biopsies of thyroid nodules [2,3], outpatient visits [3], thyroid surgery volumes [2], and radioactive iodine ablation [3]. Furthermore, virtual care has been increasingly adopted in thyroid cancer outpatient care [4]. Virtual care may be defined as "any interaction occurring remotely between patients and/or members of their circle of care, through any form of communication or information technology with the aim of facilitating or maximizing the quality and effectiveness of patient care" [5].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, physicians must rethink the strategies of approach (51). Most of these patients do not seem at a higher risk of COVID-19 infection but we still need convincing data (52). Risk-benefit analysis in each case will indicate the adequate approach considering the reality of the pandemic period (53).…”
Section: Thyroid Assessments During the Pandemic Periodmentioning
confidence: 99%
“…By contrast, in a study focusing on telemedicine to assist outpatients, Klain et al reported that the 2 referring physicians, 3 residents and 1 nurse who were usually involved in in-ward consultations at the centre they studied, were not reduced in number during the pandemic. Indeed, the teleconsultations implemented during the pandemic involved a significant workload, requiring approximately 30–40 min per teleconsultation, while the meantime for an in-ward consultation was 15–25 min ( 8 ).…”
Section: Organisational Changesmentioning
confidence: 99%
“…If the attending physician, after a teleconsultation, indicated that a more detailed assessment was necessary, patients were offered an in-ward consultation, at which all measures necessary to prevent the spread of COVID-19 were employed. The authors noticed that using these measures, the number of patients with DTC evaluated during the early months of the pandemic was only 15% less than that evaluated by in-ward examinations in the corresponding months of 2019 ( 8 )…”
Section: Impact On Diagnostic and Therapeutic Activitymentioning
confidence: 99%